"La Verdad" (2013), by Regina José Galindo: Affective Communication, the Spectator as Witness and Delegated Performance - Loureiro Álvarez, Katherine E. (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The main aim of this article is to make an approach to the notions os affective communication, the spectator as witness and delegated performance taking into account the influence of the affective turn and the social turn in performing arts. In these terms, an analysis of La Verdad, a performance executed by Regina José Galindo at the Centro Cultural de España de Guatemala on the 21st November 2013, will be performed. It is a work based on a few testimonies of women who survived the genocide caused by the armed conflict and the dictatorship of Efraín Ríos Montt.